First language translation involvement in second language word processing - Zeng, Tao; Chen, Chen; Guo, Jiashu (Frontiers in Psychology, 2022)
Previous studies have demonstrated that during the bilingual word processing, the two languages in mental lexicon are parallelly activated. However, it is under discussion whether the activated, non-target language gets involved in the target. The present study aimed to investigate the role of the first language translation (L1, the non-target one) in the second language (L2, the target one) word processing. The task of semantic relatedness judgment and lexical decision were both adopted, to explore the relation of the possible L1 involvement and the task demand. Besides, bilinguals with relatively higher and lower L2 proficiency were recruited, to clarify the potential influence of L2 proficiency. The results indicated that L1 translation was involved, but not just served as a by-product when bilinguals processing L2 words. And about the influence of L2 proficiency, there existed a better access to L1 translation in L2 word processing, as bilinguals’ L2 proficiency increased. As for the task design, the L1 translation could be partially, but not fully involved in L2 word processing, if the task design permitted. The present study supplemented the previous ones due to its participants (the intermediate bilinguals) and tasks (the task of semantic relatedness judgment and lexical decision); besides, it provided an interesting view in interpreting the “task schema” of the BIA+ model.